The Effect of the Problem Based Learning Model on Critical Thinking in Basic Chemical Laws - Nabila Al-Zahra; Buchori Muslim (Journal of Educational Sciences, 2026)
Critical thinking is an essential 21st century skills to developed in chemistry education, particularly in the topic of Basic Chemical Laws, which require scientific reasoning. This research examines how the implementation of the Problem Based Learning approach impacts students critical thinking abilities within the context of Basic Chemical Laws. This quantitative study adopted a quasi experimental method with a non equivalent control group design, in which 72 tenth grade students from SMAN 95 Jakarta were selected through purposive sampling and assigned to an experimental class (n = 36) and a control class (n = 36). The instrument consisted of 17 critical thinking essay questions that had been validated by experts and empirically tested, with a Cronbach’s Alpha reliability coefficient of 0.841. Data were analyzed using the Mann Whitney U test, normalized gain, Independent t-Test and effect sizes. The findings reveal a significant difference in critical thinking skills between the classes (p = 0.001), where the experimental class achieved a higher average N-Gain (0.30) than the control class (0.19). This model yielded a moderate positive impact, supported by a moderate effect size (Cohen's d = 0.642), proving that the PBL model successfully enhances students critical thinking skills in Basic Chemical Laws.